NaIO4/LiBr-mediated aziridination of olefins using chloramine-T - Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Shaikh, Tanveer M.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A new milder protocol for aziridination of a variety of olefins has been described. The process employs catalytic amount of sodium metaperiodate (NaIO4) as an oxidant and LiBr and chloramine-T as the bromine and nitrogen sources, respectively. Interestingly, the formation of aziridine products in all the cases studied takes place presumably through a process of 1,2-aminobromination of alkenes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aziridination; Chloramine-T; Lithium bromide; Olefin; Sodium metaperiodate

Novel synthesis and characterization of titanium superoxide and its application in organic oxidative processes - Reddy, R. Santhosh; Shaikh, Tanveer Mahamadali; Rawat, Varun; Karabal, Pratibha U.; Dewkar, Gajanan; Suryavanshi, Gurunath; Sudalai, Arumugam (Catalysis Surveys from Asia, 2010)
A novel, exceptionally stable titanium superoxide radical ion was prepared and its structure determined by FTIR, ESR, Raman spectroscopy, X-ray diffraction, thermogravimetric/differential thermal analysis and elemental analysis. This heterogeneous catalyst has been found to be effective for the selective oxidation of aromatic amines and phenols to the corresponding nitro aromatics and p-quinones, respectively. In addition, this non-toxic, inexpensive and reusable catalyst has also been used in aminobromination of olefins, which proceed to give the 1, 2-bromoaminated anti-Markovnikov product. A brief account of these results is summarized in this review.
Keywords: Amino Bromination; Anti-Markovnikov; heterogeneous catalyst; Oxidation; Titanium superoxide

NaIO4-NaN3-mediated diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones - Kamble, Dayanand A.; Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Sodium periodate and sodium azide combination has been found to be an excellent reagent system suitable for the direct diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones to produce the corresponding vicinal and geminal diazides respectively in high yields under mild reaction conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: alkenes; Aryl ketones; Geminal diazides; Sodium periodate; Vicinal diazides